Values Congruence on CSR and Its Impact on Corporate Reputation - Li, Songdi; Spry, Louise; Woodall, Tony (European Journal of Sustainable Development, 2019)
Corporate Social Responsibility (CSR) is increasingly accepted by decision makers and implemented in businesses, because it is beneficial to an organization’s profit and influence and also the perceptions and commitment of its stakeholders. Therefore, doing CSR is largely related to building a good reputation. Although the individual values of managers is more and more regarded as a driver CSR, and as the congruence between corporate values and employee values is known to impact CSR activities, the link between individual values and Corporate Reputation (CR) is an understudied topic. The purpose of this article is to propose how to investigate this issue in a higher education context. Exploring, a) to what extent university top managers and middle managers values concur in respect of CSR, and b) how this might impact on the CR which is perceived by other stakeholders are its chief focus. The proposed study is to be based on two case study universities, one in the UK and one in China. Both semi-structured interviews and surveys are proposed, representing a mixed methods approach to a complex problem. This study will benefit university top management in its CSR decision making. Keywords: personal values, organisational values, values congruence, CSR, corporate reputation